Answer:
Part A:
We are given that E is 3 more than D. This means that to get the value of E, we will simply add 3 to the value of D
Therefore:
E = D + 3
Part B:
We are given that F is 5 less than D. This means that to get the value of F, we will simply subtract 5 from the value of D
Therefore:
F = D - 5
Part C:
To get the value of E-F, we will simply subtract the equation we obtained from part B from the equation we obtained from part A
Therefore:
E - F = (D+3) - (D-5)
E - F = D + 3 - D + 5
E - F = 8
Hope this helps :)
Explanation: